Remodelling Features of Heart and Postinfarction Cardiosclerosis Type 2 Diabetes: Relationship to Gene Polymorphisms LEPR Q223R - Stanislavchuk M. A.; Al Salim A. (Львівський клінічний вісник)
Objective. To establish the features of cardiac remodeling in patients with postinfarction cardiosclerosis and type 2 diabetes based on gene polymorphism leptin receptors LEPR Q223R.